Dis-placements of the subject (Nóema, 2013)
The paper investigates the paradox of the question concerning the “place” of the subject, which cannot be asked from outside of that same place. The subject always appears to be late, away from itself, as Hegel understood. The Hegelian thought cannot in fact be simply objectified in meanings, because what it shows is the movement of the Aufhebung itself. The place of the subject appears then as an active negative, which generates its figure.
Keywords: place of the subject; Hegel; Aufhebung; negative